PELAKSANAAN MANAJEMEN OLEH PENGURUS KPRI UNIVERSITAS RIAU PEKANBARU - Nurjannah, Siti; Indrawati, Henny; Wagiman, Ngadlan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This research is done in the university of riau KPRI and since 2010 to 2011 KPRI riau university in implementing management system and functions have not been implementation fully expected. Purpose of this study was to determine the performance of the function of management at the university of riau KPRI. This study star from the month of Oktober to December 2013. The results of this study indicate that the implementation of management function at the university KPRI riau are not fully implemented well. This is caused because each of the management function still exist indicators that have not been implemented. There is still one business unit at the university of riau KPRI still not walking for 2 years and not produce anymore, and the several programs that have not been realized and the lack of motivation of the employees given the board in their job and the lack of personal attention, so that all existing management processes in KPRI university of riau.    Keywords  : Functions Management: Planning, Organizing, Actuating, Controlling